Trophoblast lineage specific expression of the alternative splicing factor RBFOX2 suggests a role in placental development. (October 2020) - Goldman-Wohl, Debra; Greenfield, Caryn; Eisenberg-Loebl, Iris; Denichenko, Polina; Jbara, Amina; Karni, Rotem; Ariel, Ilana; Yagel, Simcha
Abstract: Introduction: RBFOX2, an RNA-binding protein, controls tissue-specific alternative splicing of exons in diverse processes of development. The progenitor cytotrophoblast of the human placenta differentiates into either the syncytiotrophoblast, formed via cell fusion, or the invasive extravillous trophoblast lineage. The placenta affords a singular system where a role for RBFOX2 in both cell invasion and cell fusion may be studied. We investigated a role for RBFOX2 in trophoblast cell differentiation, as a foundation for investigations of RBFOX2 in embryo implantation and placental development. Methods: Immunohistochemistry of RBFOX2 was performed on placental tissue sections from three trimesters of pregnancy and from pathological pregnancies. Primary trophoblast cell culture and immunofluorescence were employed to determine RBFOX2 expression upon cell fusion. Knockdown of RBFOX2 expression was performed with βhCG and syncytin-1 as molecular indicators of fusion. Results: In both normal and pathological placentas, RBFOX2 expression was confined to the cytotrophoblast and the extravillous trophoblast, but absent from the syncytiotrophoblast. Additionally, we showed that primary trophoblasts that spontaneously fused in cell culture downregulated RBFOX2 expression. In functional experiments, knockdown expression of RBFOX2 significantly upregulated βhCG, while the upregulation of syncytin-1 did not reach statistical significance. Discussion: RBFOX2, by conferring mRNA diversity, may act as a regulator switch in trophoblast differentiation to either the fusion or invasive pathways. By studying alternative splicing we further our understanding of placental development, yielding possible insights into preeclampsia, where expression of antiangiogenic isoforms produced through alternative splicing play a critical role in disease development and severity. Highlights: The alternative splicing factor RBFOX2 is differentially expressed in trophoblasts. RBFOX2 mediated splicing may regulate trophoblast cell lineage determination. RBFOX2 knockdown showed upregulation of indicators of trophoblast cell fusion.